2020
DOI: 10.1002/aur.2402
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Factors and the Risk of Autism Spectrum Disorders: A Systematic Review of Existing Evidence

Abstract: Prenatal maternal diet is a critical factor in offspring neurodevelopment. Emerging evidence suggests that prenatal diet may also play a role in the etiology autism spectrum disorder (ASD). This review summarizes studies published in English that examined prenatal nutrients or maternal diet in association with ASD from PubMed as of July 2020. Thiry-six studies from nine countries were included in this systematic review; these focused on multivitamin (n = 5), prenatal vitamin (n = 3), folic acid (FA; n = 14), V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 144 publications
0
21
0
2
Order By: Relevance
“…Studies have associated an increased risk of ASD with atypical pre- and postnatal Zn and Cu metabolism [ 26 ] and found that atypical levels of essential (Zn, Mn) and non-essential (Pb) metals during prenatal development and early life in individuals with ASD are associated with long-term physiological and developmental alternations [ 27 ]. Studies have associated low maternal iron (Fe) with increased ASD risk [ 28 ]. Prenatal Zn and Cu are essential for the function of the cytoplasmic superoxide dismutase (SOD) which is essential for controlling cellular oxidative stress, while Cu is essential for ETC complex IV function.…”
Section: Prenatal Risk Factors For Asd Modulate Mitochondrial Funcmentioning
confidence: 99%
“…Studies have associated an increased risk of ASD with atypical pre- and postnatal Zn and Cu metabolism [ 26 ] and found that atypical levels of essential (Zn, Mn) and non-essential (Pb) metals during prenatal development and early life in individuals with ASD are associated with long-term physiological and developmental alternations [ 27 ]. Studies have associated low maternal iron (Fe) with increased ASD risk [ 28 ]. Prenatal Zn and Cu are essential for the function of the cytoplasmic superoxide dismutase (SOD) which is essential for controlling cellular oxidative stress, while Cu is essential for ETC complex IV function.…”
Section: Prenatal Risk Factors For Asd Modulate Mitochondrial Funcmentioning
confidence: 99%
“…ASD has a complex etiology, with both genetic and environmental contributors [2], and evidence for prenatal origins [3]. Research has linked maternal prenatal diet with ASD [4][5][6], with most of this work focused on a small number of individual nutrients and foods [4][5][6][7][8][9][10][11][12][13]. The majority of studies have suggested inverse associations with ASD, particularly for folic acid and vitamin D levels, though conflicting findings exist [5,6,[14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Many risks and protective factors have been linked to the onset of ASD in the offspring, providing suggestions for clinical practice. Numerous studies focusing on the risk of ASD in the offspring demonstrate the relevance of carefully designed maternal diet, including nutraceutical supplementation [ 50 , 225 ], the prevention and treatment of metabolic abnormalities [ 226 ], avoidance of some toxicant exposure [ 227 ]. However, there is a striking discrepancy between the plethoric literature in this field and the scarce transfer of knowledge to clinical practice.…”
Section: Lessons From Biological Research and Suggestions For Clinica...mentioning
confidence: 99%